Phytochemical Study of Traditional Medicinal Plants Used by the Kurulu Village Community, Jayawijaya Regency, Papua - Budiono, Ruly; Kusmoro, Joko; Aryani, Dian; Nur’anifah, Reni; Sukono (International Journal of Health, Medicine, and Sports, 2025)
This study explores the use of traditional medicinal plants by the community of Kurulu Village, Jayawijaya Regency, Papua. It aims to identify plant species, utilized plant parts, their phytochemical contents based on literature, and related medicinal uses. A descriptive-analytical method was applied through interviews, direct observation, and literature review. This study identified 38 medicinal plant species from 28 families utilized by the community in Kurulu Village, Papua. Various plant parts are used, with leaves being the most commonly utilized. These plants contain a range of phytochemical compounds such as alkaloids, flavonoids, saponins, tannins, and others that are effective in treating various diseases, from diarrhea to cancer. The methods of preparation include boiling, burning, pounding, steeping, squeezing, and in some cases, the plants are used directly without processing. These findings highlight the rich ethnobotanical knowledge preserved by the Kurulu community and underscore the potential of traditional medicinal plants for further pharmacological research and development.